Level Kemampuan Penalaran Spasial Siswa SMA dengan Gaya Belajar Visual dalam Menyelesaikan Masalah Geometri - Maftuh, Moh. Syukron; Alisya, Tiara Nur (Universitas Mathla'ul Anwar Banten, 2023)
The purpose of this study is to describe the level of spatial reasoning ability of high school students with a visual learning style in solving geometric problems. This research is a qualitative descriptive study. The subjects in this study were two students with a visual learning style category which was determined based on a learning style questionnaire. Data collection techniques in this study used a learning style questionnaire, TKPS, and interviews. Researchers also used data analysis techniques according to Milles & Huberman, namely data reduction, data presentation, and conclusion. Meanwhile, to check the validity of the data researcher uses source triangulation. Based on the research data obtained, it was shown that the subject imagined the design of the drawing model into real objects such as a swimming pool with stairs and a warehouse with piles of cardboard so that the subject was able to convert two-dimensional icons into three-dimensional objects. The subject showed that in the model design, there were images of blocks that had length, width, and height and there were small cubes arranged so that the subject was able to make the correct relationship between two-dimensional icons to become three-dimensional objects. The subject also determines how many unit cubes are needed to fill the block by first calculating the volume of the block and then subtracting the total number of unit cubes in the block. This the visual subject's spatial reasoning in solving geometric problems is included in the category of high-level (spatial) spatial reasoning.